2011
DOI: 10.1002/cyto.a.21044
|View full text |Cite
|
Sign up to set email alerts
|

Cytometric solutions in veterinary andrology: Developments, advantages, and limitations

Abstract: Cytometric methodologies are becoming increasingly important in veterinary andrology as means of assessing sperm function. However, as yet, flow cytometric techniques in veterinary andrology have not kept up in sophistication with those in other areas of biology and medicine. In this brief review, we consider the present state of cytometry in andrological procedures for evaluating the fertility of domestic animal sires. We outline the aspects of sperm physiology, paying particular attention to the changes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 114 publications
0
20
0
1
Order By: Relevance
“…This underlines the need for more sensitive methods to detect storage-associated changes in sperm function, particularly those focusing on responses to stimuli at the molecular level (c.f. Petrunkina et al 2005Petrunkina et al , 2007Petrunkina and Harrison 2011). It has been shown that bicarbonate stimulates boar sperm motility via a cAMPdependent pathway involving protein kinase A (Holt and Harrison 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the need for more sensitive methods to detect storage-associated changes in sperm function, particularly those focusing on responses to stimuli at the molecular level (c.f. Petrunkina et al 2005Petrunkina et al , 2007Petrunkina and Harrison 2011). It has been shown that bicarbonate stimulates boar sperm motility via a cAMPdependent pathway involving protein kinase A (Holt and Harrison 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sperm DNA must be of high quality to be able to support sustained embryo development after fertilization (Evenson, ; Evenson, Larson, & Jost, ). Flow cytometry assays have been developed to analyse viability, acrosome integrity (Hossain et al., ; MartĂ­nez‐Pastor et al., ; Petrunkina & Harrison, ) and DNA quality assessed by sperm chromatin structure assay (SCSA) (Evenson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial progress has been achieved in the optimization of female reproductive performance through better estrous detection and management of female reproductive functions (1)(2)(3). While modest additional gains can be made by further improving female fertility (4), the largest gains depend on improving the reproductive management of sires (5). Such progress can be made through improvement of semen collection, analysis, and cryopreservation, incorporating new biomarker-based andrological evaluations and state-of-the art instrumentation for automated, objective, and highthroughput semen analysis and processing (6,7).…”
Section: Introductionmentioning
confidence: 99%